Kilka uwag o związkach współczesnej intymności, prawa i polityczności (przeciwko hegemonicznemu dyskursowi prawoznawstwa dotyczącemu art. 18 Konstytucji RP z 1997 roku) - Sut, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Judgments issued based on the interpretation of art. 18 of the Polish Constitution, according to which this provision prevents institutionalization at the statutory level in Poland of same-sex relationships, and also prevents the registration in Poland of a marriage concluded abroad by persons of the same sex, and even that this provision constitutes one of the obstacles to transcription of a foreign birth certificate a child in which same-sex parents are entered as parents, lead to oppression. This inspires acritical look at this hegemonic discourse on jurisprudence regarding art. 18 of the Constitution, as well as to the demand for jurisprudence and judicial decisions to create alternative discourses in this respect — taking into account the actual, rather than minimalist or formal, implementation of freedom and equality — which in the future could take over the hegemonic position. The study includes a reference to the idea of Chantal Mouffe that the task of a democracy is to transform antagonistic relations (we/they, whose parties are enemies who do not have common points of reference) into agonic relations (we/they, whose parties are not enemies, and “opponents”). Undoubtedly, in Poland today, the confrontation between conservative circles and LGBT people and their allies is not agonizing and it is doubtful, in the current political conditions, to transfer this antagonism to the agonizing public sphere of the dispute. However, according to the author, jurisprudence (and jurisprudence) has a role to play here, which should make an effort to confront various legal discourses regarding LGBT rights. A possible loss of hegemonic position by the currently dominant legal discourse in Poland (in Article 18 of the Polish Constitution) could in the future lead to a “civilization” of public confrontation of discourses regarding claims of LGBT persons (and perhaps the transformation of the currently recorded antagonistic relationship linking conservatives with LGBT persons in an agonic relationship, and finally — changes in the law).
Keywords: relations between law and intimacy; the political; Chantal Mouffe; LGBT rights; art. 18 of the Polish Constitution; hegemonic discourse on jurisprudence